Speed of recovery in adult patients with community-acquired pneumonia; moxifloxacin versus levofloxacin - Jamal Wadi Al Ramahi; Mustafa Ramadan; Waad Jaber; Lamya Abushanab; Mohammad Mughrabi; Noor Alshamayleh; Ahmad Mulhem; Dania Momani; Mohammad Obaidat; Ghayda Haddad; Basma Khalil; Anas Zahran; et al. (Journal of Infection in Developing Countries)
Introduction: To evaluate the speed of recovery in CAP-treated adults with Moxifloxacin versus levofloxacin.